Agriculture Criteria: Climate Bonds Standard & Certification Scheme - Wollenberg, Eva Karoline; Stirling, Claire; Havlík, Petr; Vuuren, Detlef P. van; Stehfest, Elke; Dittmer, Kyle M (Climate Bonds Initiative, 2021)
ThisCriteria document provides all the requirements that must be met for agriculture related assets and projects to be awarded Climate Bonds Certification. The purpose is to provide instruction to issuers and verifiers about the requirements of the Agriculture Criteria. The Criteria document is supported by a background document that captures the various dialogues and inputs and substantiates the reasoning behind the requirements set in the Agriculture Criteria.